Technology and diversity in higher education new challenges - Inoue, Yukiko (Gale virtual reference library, 2007)
"This book examines current and effective educational practices as well as new challenges involving emerging technologies in increasingly diverse learning environments in higher education and the impact of the explosion of technology. These challenges are well documented in this collection of essays, case studies, and research reports"--Provided by publisher.